2003
DOI: 10.1098/rspb.2002.2271
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator attraction in a sexually deceptive orchid by means of unconventional chemicals

Abstract: Ophrys flowers mimic virgin females of their pollinators, and thereby attract males for pollination. Stimulated by scent, the males attempt to copulate with flower labella and thereby ensure pollination. Here, we show for the first time, to our knowledge, that pollinator attraction in sexually deceptive orchids may be based on a few specific chemical compounds. Ophrys speculum flowers produce many volatiles, including trace amounts of (omega-1)-hydroxy and (omega-1)-oxo acids, especially 9-hydroxydecanoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
149
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(158 citation statements)
references
References 21 publications
7
149
0
2
Order By: Relevance
“…They produce the behaviourally active components of the sex pheromone of receptive females of the imitated insect species to attract males and elicit mating behaviour. During the subsequent copulation attempt, the so-called pseudocopulation, the pollinaria become attached to the male's body and pollen is transferred upon visitation of subsequent flowers (Kullenberg, 1961;Ayasse et al, 2003;Schiestl et al, 2004;Schiestl, 2005). Pollinator attraction in these orchids is very specific as only males of the target species are attracted while other flower visitors do not respond to the odour bouquet.…”
Section: Introductionmentioning
confidence: 99%
“…They produce the behaviourally active components of the sex pheromone of receptive females of the imitated insect species to attract males and elicit mating behaviour. During the subsequent copulation attempt, the so-called pseudocopulation, the pollinaria become attached to the male's body and pollen is transferred upon visitation of subsequent flowers (Kullenberg, 1961;Ayasse et al, 2003;Schiestl et al, 2004;Schiestl, 2005). Pollinator attraction in these orchids is very specific as only males of the target species are attracted while other flower visitors do not respond to the odour bouquet.…”
Section: Introductionmentioning
confidence: 99%
“…The specific pollinator responses of Andrena nigroaenea and A. flavipes to the closely related and sympatric O. fusca and O. bilunulata, respectively (Schiestl and Ayasse 2002), are mediated by different relative amounts of alkenes. By contrast, in the floral odor of the more distantly related O. speculum, highly specific oxygenated carboxylic acids attract scoliid wasps as pollinators (Ayasse et al 2003).…”
mentioning
confidence: 99%
“…However, floral odor is the primary signal for pollinator attraction. Floral odor extracts and synthetic blends of those odors can induce attraction and copulatory behavior in patrolling male hymenoptera with only crude visual or tactile cues (Kullenberg and Bergströ m 1976;Borg-Karlson 1990;Schiestl et al 1999;Ayasse et al 2000Ayasse et al , 2003. It is also the floral odor traits that are responsible for maintaining species boundaries through the attraction of a single or very few pollinator species (Paulus and Gack 1990a;Schiestl and Ayasse 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(DELFORGE 2006). The species is pollinated by the wasp Dasyscolia ciliata (Scoliidae, Hymenoptera) and this relationship is highly species-specific (POUYANNE 1917, AYASSE et al 2003, BAUMANN et al 2006, PAULUS 2007. It has been found that the western variant is pollinated by D. ciliata ssp.…”
Section: Introductionmentioning
confidence: 99%